До 100-річчя Національної академії наук України – колиски вітчизняної науки і техніки - Баранов, М.І.; Розов, В.Ю.; Сокол, Є.І. (Електротехніка і електромеханіка, 2018)
Зроблено короткий науково-історичний нарис про створення, розвиток і структуру Національної академії наук (НАН)
України. Відзначена важлива роль НАН України в розвитку суспільства та міжнародній науково-технічній співпраці.
Наведено основні наукові досягнення вчених НАНУ в різних областях науки, а також коротко викладено результати
наукових досліджень, які досягнуті за останні кілька років Інститутом технічних проблем магнетизму НАН України
та Інститутом іоносфери НАН і МОН України (м. Харків). Висвітлено співпрацю вчених-електротехніків НТУ
«ХПІ» з науковими установами НАН України. Приведен краткий научно-исторический очерк о создании, развитии и структуре Национальной академии наук (НАН)
Украины. Отмечена важная роль НАН Украины в развитии общества и международном научно-техническом сотрудничестве. Приведены основные научные достижения ученых НАНУ в различных областях науки, а также кратко изложены результаты научных исследований, достигнутые за последние несколько лет Институтом технических проблем магнетизма НАН Украины и Институтом ионосферы НАН и МОН Украины (г. Харьков). Освещено
сотрудничество ученых-электротехников НТУ «ХПИ» с научными учреждениями НАН Украины. Purpose. Preparation of short scientifically-historical essay about
creation and development of the National Academy of Sciences
(NAS) of Ukraine. Methodology. Known scientific methods of collection, analysis and analytical treatment of scientific and technical
information, touching creation and development of NAS of Ukraine
and resulted in scientific monographs, journals and internetreports. Results. A short scientifically-historical essay is presented
about creation and development of NAS of Ukraine. The main scientific achievements of NAS of Ukraine in various fields of science are
presented. It is pointed that a large scientifically-organizational
contribution to these achievements brought by present President of
NAS of Ukraine, Academician B.Ye. Paton, his 100th Birthday (27
November, 2018) coincides surprising appearance with the 100th
anniversary of NAS of Ukraine. An important role of NAS of
Ukraine in the development of society and international scientific
and technical cooperation was noted. The results of scientific research, achieved over the past few years by the Institute of Technical Problems of Magnetism of the NAS of Ukraine (Kharkiv), as
well as by the Institute of Ionosphere of the NAS and Departments
of education and science (DES) of Ukraine (Kharkiv) are briefly
presented. The research cooperation in the field of electrical engineering of NTU «KhPI» with scientific institutions of the NAS of
Ukraine is highlighted. Originality. Certain systematization is executed of known from scientific journals and other mass of scientific
and technical materials, touching the results of activity of research
workers of institutes of NAS of Ukraine in the last few years. Practical value. Scientific popularization and deepening for the students
of higher school, engineer-technical and scientific workers, working
in the different sectors of economy of country, scientific and technical knowledge in an area of physical-technical and mathematical
sciences, chemical and biological sciences, and also social and
humanitarian sciences, extending their scientific range of interests
and further development of scientific and technical progress in society